Desenvolvimento de metodologias voltamétricas para determinação simultânea de carbofurano e metomil usando eletrodo de diamante dopado com boro - Santos, Janete Clair da Silva (2016)
Carbofuran (2,2-dimethyl-2,3-dihydro-1-benzofuran-7yl-methylcarbamate) is a kind of pesticide with nematicide and acaricide power, belonging to the chemical group of benzofuranyl methylcarbamate; methomyl {(R, S)-methyl-N- {[(methylamino) carbonyl] oxy} ethanimidothioate} is also a pesticide with acaricide power, it is inserted into the methylcarbamate oxime chemical group. They present high toxicity, and both are inserted in class I of toxicity and class II of environmental risks. In general, their detection and analytical determinations are carried with chromatographic methods, electrophoretic, fluorometric, spectrophotometric fluorescence X-rays and electroanalytical. In this study, one has made use of boron-doped diamond electrode due to its inherent properties: wide potential range and low adsorption of organic molecules. Thus, one has studied the electrochemical behavior of carbofuran and methomyl using cyclic voltammetry, square-wave voltammetry, differential pulse voltammetry, being developed methodologies for simultaneous studies by SWV and DPV. Throughout the pH analysis by SWV technique, one observed oxidation process of carbofuran (Ep1 ≈ + 1.3 V vs. EAg/AgCl) and the same process for the methomyl (Ep1 ≈ + 1.6 V vs. EAg/AgCl) in DDB cathodically polarized. A simultaneous methodology using SWV was developed, being the best analytical conditions: pH 1.0 (sulfuric ac. 0.1 mol L-1), f = 150 s-1, ΔEs = 4 mV, ΔEp = 30 mV, td = 10 s, obtaining a linear range of 2.5 x 10-6 to 7.9 x 10-5 mol L-1. Also, an alternative methodology has been developed with the DPV technique. The best VPD analysis conditions that provided the most sensitive voltammetric response were: pH 1.0 (sulfuric ac. 0.1 mol L-1), TI = 0.2, ΔEs = 4 mV, ΔEp = 50 mV, td = 10s, with a linear range of 2.48 x 10-4 to 1.42 x 10-4 mol L-1. This work shows that the two proposed methodologies are feasible. Keywords: methomyl, carbofuran, boron-doped diamond electrodes, voltammetry.